Going national: universal jurisdiction and the principle of complementarity in the Rome Statute of the International Criminal Court - Rolffs, Lina (Global Risk Governance Programme, 2025)
In a historical moment, after a couple of decades of development from Nuremberg to the ad hoc tribunals for the former Yugoslavia and Rwanda, the permanent International Criminal Court (ICC) set to work in The Hague in 2002, to fight impunity for the most atrocious crimes against international law, having an impact on the international community as a whole.1 This has been welcomed with high expectations from the civil society.2 However, negotiations on an international multilateral level require compromise, and compared to the ideal of a Court with unlimited resources and jurisdiction, the final form of the ICC does not seem to be able to live up to the expectations. The budget of this international institution is very limited, and could and should only cover the costs of proceedings for the very masterminds of crimes,3 which are in turn all too often only possible because of the participation of so many individual criminals.